Respuesta :
For this case we have that by definition, the point-slope equation of a line is given by:
[tex]y-y_ {0} = m (x-x_ {0})[/tex]
We have as data that:
[tex](x_ {0}, y_ {0}): (- 6, -3)\\m = 4[/tex]
Substituting in the equation we have:
[tex]y - (- 3) = 4 (x - (- 6))\\y + 3 = 4 (x + 6)[/tex]
Finally, the equation is: [tex]y + 3 = 4 (x + 6)[/tex]
Answer:
[tex]y + 3 = 4 (x + 6)[/tex]
[tex]\huge{\boxed{y+3=4(x+6)}}[/tex]
Point-slope form is [tex]y-y_1=m(x-x_1)[/tex], where [tex]m[/tex] is the slope and [tex](x_1, y_1)[/tex] is a known point on the line.
Substitute in the values. [tex]y-(-3)=4(x-(-6))[/tex]
Simplify the negative subtraction. [tex]\boxed{y+3=4(x+6)}[/tex]